Chicka chicka boom boom - Martin, Bill, 1916-2004.; Archambault, John.; Ehlert, Lois (New York : Simon & Schuster Books for Young Readers, 1989)
An alphabet rhyme/chant that relates what happens when the whole alphabet tries to climb a coconut tree.
Keywords: Alphabet; Stories in rhyme